Macroeconomic policies and poverty reduction - Ashoka Mody; Catherine A. Pattillo (Routledge, 2006)
In this volume, world-renowned contributors, including Martin Ravallion, Michael Kremer and Robert Townsend, deal with the institutional characteristics of poverty resulting from the time pattern of aid, the nature of financial systems and the political economy of budgetary decisions. Going beyond the traditional literature on poverty, this original book deals with themes of broad interest to both scholars and policymakers in a clear yet technically sophisticated manner. Departing from conventional methods employed in poverty studies, these innovative essays enquire into the institutional characteristics of poverty, and using current case studies, they examine the crucial idea that periods of crises seriously affect poverty.
Keywords: 330; trade; liberalisation; income; distribution; heavily; indebted; poor; countries; reduction; exchange; Wirtschaftspolitik; Wirtschaftswachstum; Armutsbekämpfung; Entwicklungsländer